2020
DOI: 10.1007/s11696-020-01376-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of ion-exchange resin beads to produce magnetic adsorbents

Abstract: Heavy metal ions are among the most dangerous contaminants, which can cause serious health problems. In this work, ion-exchange resin beads were used as supports for magnetite (Fe3O4) synthesis to produce heavy metal adsorbents which can be easily separated by magnetic field. The first step of the magnetite preparation was the replacement of hydrogen ions with Fe2+ and Fe3+ ions on the sulfonic acid groups of the resin. In the second step, magnetite particle formation was induced by coprecipitating the iron io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Considering the sulphonic sorbents structure and the mechanism suggested by Taha (2021), 75 Sikora et al (2021), 76 and Zhang et al (2022), 77 the suggested mechanisms for Co and Sr sorption are represented in reactions (15) and (16) depending on whether they are bonded to one or two functional groups. A similar mechanism to the one described in reaction (15) is expected for Cs and Rb (as Cs + and Rb + ) by the substitution of the Na + in the sorbent functional groups obtaining, in that case, a neutral molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the sulphonic sorbents structure and the mechanism suggested by Taha (2021), 75 Sikora et al (2021), 76 and Zhang et al (2022), 77 the suggested mechanisms for Co and Sr sorption are represented in reactions (15) and (16) depending on whether they are bonded to one or two functional groups. A similar mechanism to the one described in reaction (15) is expected for Cs and Rb (as Cs + and Rb + ) by the substitution of the Na + in the sorbent functional groups obtaining, in that case, a neutral molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The isotherm models evaluated in this study were fitted to literature data [tetracycline adsorption data (Ma et al 2022); nickel adsorption data (Sikora et al 2021)] using a nonlinear least-squares fitting algorithm to minimize the sum of squared residuals (SSR) defined by Eq. ( 8), where qi,obs is the ith observed value of q, qi,fit is the ith value of q calculated from a particular isotherm model, and z is the number of data points.…”
Section: Data Fittingmentioning
confidence: 99%
“…In this second example, the selected data set describes the adsorption of nickel ions by a magnetic ion exchanger (Sikora et al 2021). The adsorption isotherm, depicted in Fig.…”
Section: Isotherm Data With An Apparent Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…In India ground water is used for domestic as well as agricultural purposes. Heavy metals ions such as iron, cobalt, cadmium, lead, mercury, chromium, selenium, arsenic, copper and zinc are invariably present in groundwater.These metal ions are considered to be toxins when they enter inside the body exceeding the prescribed limit, wherein they start causing illness [1][2][3]. Some of the heavy metal ions such as iron, cobalt, cadmium, lead, mercury, chromium, selenium and arsenic were found in industrial effluent of Okhla industrial area phase-II of Delhi NCR Region, India and because of this the groundwater of nearby areas is also contaminated [4].…”
mentioning
confidence: 99%